Association between diabetes mellitus and total hip arthroplasty outcomes: an observational study using the US National Inpatient Sample - Jasvinder A Singh; Sumanth Chandrupatla; Kranti Rumalla (BMJ Open)
Objectives To investigate the association of diabetes with postoperative outcomes in patients undergoing primary total hip arthroplasty (THA).Design Retrospective cohort study using data from the US National Inpatient Sample (NIS).Setting Study cohort was hospitalisations for primary THA in the USA, identified from the 2016–2020 NIS.Participants We identified 2 467 215 adults in the 2016–2020 NIS who underwent primary THA using International Classification of Diseases, 10th Revision codes. Primary THA hospitlizations were analysed as the overall group and also stratified by the underlying primary diagnosis for THA.Outcome measures Outcome measures of interest were the length of hospital stay>the median, total hospital charges>the median, inpatient mortality, non-routine discharge, need for blood transfusion, prosthetic fracture, prosthetic dislocation and postprocedural infection, including periprosthetic joint infection, deep surgical site infection and postprocedural sepsis.Results Among 2 467 215 patients who underwent primary THA, the mean age was 68.7 years, 58.3% were female, 85.7% were white, 61.7% had Medicare payer and 20.4% had a Deyo-Charlson index (adjusted to exclude diabetes mellitus) of 2 or higher. 416 850 (17%) patients had diabetes. In multivariable-adjusted logistic regression in the overall cohort, diabetes was associated with higher odds of a longer hospital stay (adjusted OR (aOR) 1.38; 95% CI 1.35 to 1.41), higher total charges (aOR 1.11; 95% CI 1.09 to 1.13), non-routine discharge (aOR 1.18; 95% CI 1.15 to 1.20), the need for blood transfusion (aOR 1.19; 95% CI 1.15 to 1.23), postprocedural infection (aOR 1.62; 95% CI 1.10 to 2.40) and periprosthetic joint infection (aOR 1.91; 95% CI 1.12 to 3.24). We noted a lack of some associations in the avascular necrosis and inflammatory arthritis cohorts (p>0.05).Conclusion Diabetes was associated with increased healthcare utilisation, blood transfusion and postprocedural infection risk following primary THA. Optimisation of diabetes with preoperative medical management and/or institution of specific postoperative pathways may improve these outcomes. Larger studies are needed in avascular necrosis and inflammatory arthritis cohorts undergoing primary THA.